Fasakh Dan Batalnya Suatu Perkawinan (Analisis KHI dan UU Perkawinan) - Muhammad, Muhammad (Universitas Pahlawan Tuanku Tambusai, 2025)
Marriage is a bond between husband and wife which aims to bind each other. In a marriage, problems often occur which lead to the nullification of the marriage. Law number 1 of 1974 and KHI have expressly regulated matters that can cause marriage to be nullificated. This paper uses a qualitative method (library research) using a descriptive approach. This aims to explore and discover things that might happen in a marriage and could cause the marriage to be annulled as stated in the formulation of Law number 1 of 1974 and KHI. In this article, it can be found that the Marriage Law and KHI provide a straightforward description of the stages of nullification of marriage, the reasons for the marriage and the effects of the marriage nullification. Between Law No. 1 of 1974 and the compilation of Islamic law they do not conflict but complement each other and have become qanun (regulations ratified by the government), and the annulment of marriage is sometimes null and void because it violates religious provisions regarding the prohibition of marriage and sometimes it can also be cancelled. because several matters are administrative in nature and must go through a court decision. Cancellation of marriage as regulated in the KHI and the Marriage Law has an impact not only on the husband and wife but also on other parties, such as children and property.